Precalculus (6th Edition)

Published by Pearson
ISBN 10: 013421742X
ISBN 13: 978-0-13421-742-0

Chapter R - Review of Basic Concepts - R.4 Factoring Polynomials - R.4 Exercises - Page 44: 91



Work Step by Step

Substitute $u=m^{2}.$ $m^{4}-3m^{2}-10=u^{2}-3u-10=...$ When factoring $x^{2}+bx+c$, we search for factors of $c$ whose sum is $b,$ Here, these factors are $-5$ and $+3$ $...=(u-5)(u+3)$ ... bring back m $=(m^{2}-5)(m^{2}+3)$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.